POLYVINYLPYRROLIDONE-FERROCYANIDE CATALYSTS FOR CYCLOHEXANE OXIDATION - Tastanova L.K.; Zharmagambetova A.K.; Orynbassar R.O.; Apendina A.K.; Zhumabekova. A.K. (Academic Scientific Journal of Chemistry, 2019)
. Catalysts for cyclohexane oxidation are developed. Polymer-ferrocyanide catalysts fixed on various mineral supports are prepared by the adsorption method. Properties of synthesized catalysts are studied in cyclohexane oxidation with hydrogen peroxide. Reaction is carried out under mild conditions: at 40 °C and atmospheric pressure. All prepared polymer-metal catalysts supported on inorganic substrates are active in the process of cyclohexane oxidation. Polymer-metal complex fixed on alumosilicate Siral-20 shows 14% more activity than the system fixed on Siral-40. However selectivity of catalyst 5% K4[Fe(CN)6] -PVP/Siral-40 is much higher. Under equal conditions, its selectivity for cyclohexanone is 83.4%, whereas selectivity for cyclohexanone of 5% K4[Fe(CN)6]-PVP/Siral-20 is only 61.7%. Catalyst fixed on γ-Al2O3 demonstrates less activity (25.5%) and selectivity than aluminum silicates (cyclohexanone : cyclohexanol ratio is 1.2 : 1). At the same time, with a sufficiently high selectivity for cyclohexanone (70.4%), 5% K4[Fe(CN)6]-PVP/SiO2 shows the conversion which is only 17.2%. The effect of acidic properties of carrier surface on selectivity is studied. It is established that the nature of support (acidic properties of surface) has a significant effect on activity and selectivity of synthesized catalysts. Polyvinylpyrrolidone-ferrocyanide complex 5%K4[Fe(CN)6]-PVP/Siral-40 exhibits the best catalytic properties. The conversion of cyclohexane is 42.9%, selectivity for cyclohexanone is 83.4% and cyclohexanone : cyclohexanol ratio is 5: 1.